Rhodium-Catalyzed Spirocyclization of Maleimide with N-Aryl-2,3-dihydrophthalazine-1,4-dione to Access Pentacyclic Spiro-Succinimides - Mandal, Sanjay K. (Wiley, 2021)
A one-pot spirocyclization of 2-aryl-2,3-dihydrophthalazine-1,4-diones with maleimides was achieved via RhIII-catalyzed sequential ortho-alkenylation followed by intramolecular aza-Michael-type addition/protonation process. The featured strategy furnishes a series of diversely decorated spiro[indazolo[1,2-b]phthalazine-13,3′-pyrrolidine]-2′,5′,6,11-tetraones in high yields from a variety of 2-aryl-2,3-dihydrophthalazine-1,4-diones and N-aryl/alkyl maleimides, which can be scaled-up easily. Isolation and characterization of a maleimide-coordinated five-membered rhodacyclic intermediate provided a strong evidence for the proposed mechanism of the reaction.
Only IISER Mohali authors are available in the record.
Keywords: Rhodium-Catalyzed; Spiro-Succinimides